Global Governance on The Responses Toward Illegal Organ Transplantation and Trafficking in Pakistan - Katong Ragawi Numadi; Ni Putu Devi Maharani (Insignia: Journal of International Relations, 2025)
Illegal organ trafficking is a complex transnational criminal issue faced by Pakistan. The process of globalization, coupled with various socio-political and economic problems, has created the preconditions for the rapid growth of human organ trafficking in several regions in Pakistan. Consequently, the number of cases and victims of illegal organ transplantation and trafficking in Pakistan continues to rise. This study aims to analytically describe several efforts to combat the existence of illegal organ trafficking criminal networks in Pakistan within a global governance framework. The efforts involve not only strengthening Pakistani government policies but also implementing international cooperation and initiatives from civil society organizations and networks. In examining the global governance aspects of addressing transnational illegal organ trafficking in Pakistan, this study employs a descriptive qualitative method by using a literature review technique. The initial research revealed that the Pakistani government has taken various measures to eradicate illegal organ trafficking criminal networks in Pakistan. One of which is the creation of specific national legal regulations, which become the basis for strengthening preventive policies and intensifying prosecution actions. Internationally, Pakistan actively participates in a series of international anti-human trafficking and anti-organ trafficking frameworks and protocols. Meanwhile, the role of civil society organizations, particularly from medical professionals such as the Sindh Institute of Urology and Transplantation (SIUT Pakistan), cannot be ignored in the advocacy and legislative processes to address the threat of transnational human organ trafficking in Pakistan. Keywords: Pakistan, Transplantation, Organ Trafficking, THOTA.